2020
DOI: 10.1109/access.2020.2981615
|View full text |Cite
|
Sign up to set email alerts
|

A 16 × 16-Element Slot Array Fed by Double-Layered Gap Waveguide Distribution Network at 160 GHz

Abstract: In this article, a slot array with double-layered full-corporate-fed distribution network by ridge gap waveguide (RGW) in the G-band is presented. The array antenna proposed in this article contains 16 × 16-element radiation slots fed by air-filled ridge gap waveguide distribution network that achieves highefficiency. Gap waveguide technology avoids the demand for perfect electrical contact in millimeter waves, therefore the expensive diffusion bonding and the laser welding processes are not demanded. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Moreover, the integration of multilayer substrate-integrated gap waveguide (SIGW) horn antennas and hybrid technologies amalgamating SIW and PRGW have expanded the design horizons of mm-wave antennas. By leveraging elevated-SIGW structures and triangular slot configurations, engineers have achieved wide bandwidth coverage and enhanced gain performance, paving the way for novel applications in diverse scenarios [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Illustrating the breadth of possibilities, Figure 5 showcases metallic GW antennas tailored to various mm-wave applications, addressing specific requirements and challenges.…”
Section: Mm-wave Antennas With Diverse Polarizationsmentioning
confidence: 99%
“…Moreover, the integration of multilayer substrate-integrated gap waveguide (SIGW) horn antennas and hybrid technologies amalgamating SIW and PRGW have expanded the design horizons of mm-wave antennas. By leveraging elevated-SIGW structures and triangular slot configurations, engineers have achieved wide bandwidth coverage and enhanced gain performance, paving the way for novel applications in diverse scenarios [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Illustrating the breadth of possibilities, Figure 5 showcases metallic GW antennas tailored to various mm-wave applications, addressing specific requirements and challenges.…”
Section: Mm-wave Antennas With Diverse Polarizationsmentioning
confidence: 99%
“…Over the past several years, there has been an increasing amount of interest in developing a fixed beam array antenna based on GW technology for various applications. Several antenna configurations based on different GW technology have been successfully devised, ranging from X-band to D-band and beyond [26]- [29]. The slot antenna has been essential in the development of array antennas based on the conventional metallic waveguide because it is a straightforward implementation.…”
Section: A Fixed Beam Slot Array Antennamentioning
confidence: 99%
“…14 The fabrication process of full metal antenna arrays based on the conventional milling technique is not desirable due to the high accuracy requirement, especially in the mmWave and above frequency bands. 15,16 Nevertheless, reported studies revealed that the arrays had to be split into multiple pieces during fabrication based on conventional mechanical technology. As a result, the wave leakage caused by the possible air-gaps between adjacent layers is difficult to prevent entirely for the assembled prototypes, and thus deteriorating the operating performance of the arrays.…”
Section: Introductionmentioning
confidence: 99%
“…High power handling capacity and structural robustness make these antennas good candidates for long‐distance communication systems such as base stations, radar, and satellite communications 14 . The fabrication process of full metal antenna arrays based on the conventional milling technique is not desirable due to the high accuracy requirement, especially in the mmWave and above frequency bands 15,16 . Nevertheless, reported studies revealed that the arrays had to be split into multiple pieces during fabrication based on conventional mechanical technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation